Solving an old dilemma: are the two sympatric species Lema apicalis and L. reticulosa (Coleoptera, Chrysomelidae, Criocerinae) morphotypes of a single species? - Von Groll, Elisa (Zootaxa, 2021)
Two species of Lema (Quasilema), L. apicalis Lacordaire, 1845 and L. reticulosa Clark, 1866 are compared and found to be identical based on morphology and behaviour, although they exhibit different colour patterns (Lema (subgenus Quasilema) apicalis Lacordaire, 1845 = Lema (Quasilema) reticulosa Clark, 1866 new synonym). These morphs are sympatric, with distribution in southern Brazil, Argentina, Paraguay, and Uruguay, and feed and oviposit on the same host plant (Vassobia breviflora (Sendtn.) Hunz (Solanaceae)).